Design and selection criteria of main parachute for re-entry space payload - Pratap M.; Agrawal A.K.; Kumar S. (My University, 2025)
Parachutes are used as a decelerator in the re-entry, descent, and landing of space recovery payloads, providing stability and desired descent rate for a safe landing. The selection of the main parachute is the most critical and important part of the space module recovery system. Parachute size is restricted by the required landing speed, materials, and weight of the payload. Parachute materials are selected based on the various forces experienced by the parachute. An investigation has been carried out to design a parachute system which gives less impact velocity, less angle of oscillation and less impact load for the landing of a crew module. Therefore, in this paper, selection criteria for the main parachute have been discussed considering recovery of re-entry space payload of 500 kg (unmanned) and 3500 kg (manned) class. Based on analysis carried out on the parachute size, canopy filling time, velocity reduction, peak deceleration, and opening shock, authors have proposed a unique type of solid canopy with slots (slots of the minimum area equivalent to geometry porosity) for the main parachute rather than a complex ringsail or disk-band type canopy. With this new concept, the parachute has been designed, developed and qualified through testing, trials and maiden flight of space capsule in LEO and is propose to use in the next manned space mission program. © 2019, DESIDOC